2021
DOI: 10.3389/fonc.2021.773644
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the Promoter of miR-338-5p Mediates Aberrant Expression of ETS-1 and Is Correlated With Disease Severity Of Astrocytoma Patients

Abstract: The pro-oncogene ETS-1 (E26 transformation-specific sequence 1) is a key regulator of the proliferation and invasion of cancer cells. The present work examined the correlation of the aberrant expression of ETS-1 with histological or clinical classification of astrocytoma: grade I (pilocytic astrocytoma), grade II (diffuse astrocytoma), grade III (anaplastic astrocytoma), and grade IV (glioblastoma multiforme). MicroRNA, miR-338-5p, was predicted by an online tool (miRDB) to potentially target the 3’ untranslat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Nevertheless, we must still elaborate on the causal relationship between the methylation of the miR-23 promoter region and the expression of uPA in the future. Wang et al found that DNA methyltransferase 1 can mediate the methylation of the miR-338-5p promoter region, cause the loss of miR-338-5p expression, and ultimately cause a high level of ETS-1 in gliomas ( 63 ). For this reason, in the future, our research group will investigate (1) DNMT-1 expression detection in MM; (2) the effects of DNMT-1 overexpression or knockdown on the expression of miR-23, and on the miR-23 promoter’s methylation; and (3) the recruitment of DNMT-1 to the CpG islands in the promoter region of miR-23.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we must still elaborate on the causal relationship between the methylation of the miR-23 promoter region and the expression of uPA in the future. Wang et al found that DNA methyltransferase 1 can mediate the methylation of the miR-338-5p promoter region, cause the loss of miR-338-5p expression, and ultimately cause a high level of ETS-1 in gliomas ( 63 ). For this reason, in the future, our research group will investigate (1) DNMT-1 expression detection in MM; (2) the effects of DNMT-1 overexpression or knockdown on the expression of miR-23, and on the miR-23 promoter’s methylation; and (3) the recruitment of DNMT-1 to the CpG islands in the promoter region of miR-23.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies had shown that DNA methylation was significantly different in normal cells and different subtypes of gliomas, and extensive hypermethylation and hypomethylation of different CpG islands are characteristic of glioma (34). For example, Wang et al demonstrated that hypermethylation of the miR-338-5p promoter regulated the aberrant expression of ETS-1, which was a key regulator of tumor cell proliferation and invasion, and was associated with prognosis of astrocytoma patients (35). There was also a public database-based bioinformatics analysis showing that PODNL1 methylation acted as a prognostic biomarker and correlates with immune infiltration and immune checkpoints in LGG (36).…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] However, another research found that the inhibition of methylated miR-338-5p-5p in the promoter region was related to AOA invision. [ 43 ] It was because of these inconsistent prognostic results that we further used a meta-analysis to research the prognostic value of CIMP in gliomas.…”
Section: Discussionmentioning
confidence: 99%